RAPD Analysis for Genetic Variability Detection of Mutant Soybean (Glycine max (L.) Merr) - Didik Wahyudi; Lia Hapsari; S. Sundari (Universitas Gadjah Mada, 2020)
This study aimed to detect and evaluate the genetic mutation from mutagenized soybean by RAPD markers. Soybean seeds of “Grobogan” variety were treated with two different concentrations of EMS (0.5% and 1%) and three incubation times (4, 6 and 8 h). DNA whole-genome was isolated from young leaf seedling with the Qiagen DNeasy Plant Mini Kit. Twenty OPA primers (OPA-1 to OPA-20) were used for DNA amplification. The results showed that EMS treatments successfully generated genetic variation in soybean, which indicated by high values of PIC, EMR, and MI. RAPD primers that effective to detect the mutation were OPA-2, OPA-07, OPA-10, OPA-11, OPA-12, OPA-13, OPA-14, OPA-15, OPA-16, OPA-18 and OPA-20. The band expression of those primers was exhibited a stronger intensity along with increasing of EMS concentration and incubation time used in this study. Treatment of 0.5% EMS in 6 hours incubation was successfully generated soybean mutants with the lowest genetic similarity compared to the wild-type. Thus, this study provides a new approach to generate genetic variability in soybean and has the potential to improve for soybean breeding program.